INTEGRATION OF MULTIMEDIA TOOLS IN THE EDUCATIONAL PROCESS AND THEIR IMPORTANCE - Umedova M.E.; Jalolov N.N. (The Conference Hub, 2025)
The educational system undergoes continuous transformations while needing the integration of modern technological solutions. The effectiveness of learning processes grows through multimedia tools because they help students develop both interest and motivation levels. The pedagogical technologies involving multimedia tools such as images, videos, audio and animations and other visual materials help explain complex subjects in an accessible and understandable format. The implementation of multimedia tools activates student cognitive processes while enabling better knowledge retention through a stronger educational connection between instructors and their students.